The role of TRPV1 in improving VSMC function and attenuating hypertension. Issue 2 (March 2015) - Zhang, Ming-Jie; Yin, Yan-Wei; Li, Bing-Hu; Liu, Yun; Liao, Shao-Qiong; Gao, Chang-Yue; Li, Jing-Cheng; Zhang, Li-Li
Abstract: The transient receptor potential vanilloid type 1 (TRPV1) channel, a ligand-gated cation channel of the TRP subfamily, can be activated by multiple stimuli, including capsaicin. Currently, cumulative studies have demonstrated an interesting link between TRPV1 and cardiovascular diseases, including hypertension. Additionally, the protective effect of TRPV1 against hypertension and its related disorders has been proved to be partly involved with the improved action of vascular smooth muscle cells (VSMCs). This review focuses on the current knowledge of TRPV1 in improving VSMC function and attenuating hypertension.